MENINGKATKAN KEMAMPUAN SOSIAL EMOSIONAL ANAK USIA DINI MELALUI KEGIATAN KOLASE - Indah Afrilia; Khadijah; Elfina Yanti; Salsabila Siregar; Ririn Widayanti (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze how to improve the social emotional abilities of young children through collage activities. The method in this research is a qualitative method with a descriptive type. Then the data collection technique in this research is library research or literature study, where the method uses a library approach to collect data from the library, reading and taking notes. The analysis technique used in this research is the content of the article which is an in-depth discussion of the content of written information. The results of this research show that collage activities can improve the social emotional abilities of young children by collaborating with hand, eye and art activities so that they can stimulate fine motor development for normal and disabled children. This activity is carried out with Gutu guidance so that the child's patience when gluing or matching patterns when carrying out collage activities can be optimal and get good and neater collage results.